Tx/Rx: Generation and Correlation of aCostas Array FM CodeUsing FPGA Spatran-3 Technology - Thamir R. Saeed (Engineering and Technology Journal, 2012)
This paper describes a real time generation and correlation of Costas array FM code pulse compression using Field Programmable Gate Array (FPGA) for implementation, which provides the flexibility, reconfigure ability and reprogram ability. This implementation contains two parts, the first Part, to generate. Number of frequency sequences, which can use as Costas, where, this part was built in transmitter side. The second part of implementation contains three stages in the receiver side; range determination, correlation and Doppler measurement to the replica of Tx-signal. The tested work was taken for eight digits and two cases of frequency shift (1&2) with an eight time shift for each one. This implementation was built by using VHDL editor for Spartan-3 with IC XC3S200. The clock is 20nsec and can use less than that time.